Social risk effects: The "experience of social risk" factor / Florian Diekert, Timo Goeschl, and Christian König-Kersting - Florian Diekert; Timo Goeschl; Christian König-Kersting (University of Heidelberg, Department of Economics, 2021)
Anticipating "social risk", or risk caused by humans, affects decision-making differently from anticipating natural risk. Drawing upon a large sample of the US population (n=3,982), we show that the phenomenon generalizes to risk experience. Experiencing adverse outcomes caused by another human reduces future risk-taking, but experiencing the same outcome caused by nature does not. While puzzling from a consequentialist perspective, the Experience of Social Risk Factor that we identify deepens our understanding of decision-making in settings in which outcomes are co-determined by different sources of uncertainty. Our findings imply that a unifying theory of social risk effects requires new explanations.
urn:nbn:de:bsz:16-heidok-303095
Keywords: C72; C90; D81; D91; 330; Social risk; risk experience; decision-making under risk; behavioral economics; experiment